AgileQube: An approach for specification and detection of agile smells - Telemaco, Ulisses; de Oliveira, Toacy Cavalcante (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
This paper presents the thesis entitled “AgileQube: an approach for specification and detection of agile smells” (Telemaco 2020 [24]) submitted to COPPE/UFRJ as part of the requirements for obtaining the degree of Doctor of Science (D.Sc.). In the thesis, we aimed to contribute to the area of agility assessment (which is an investigation on how a company or a team is adopting agile practices) in the following way: first, we investigated existing agility assessment approaches and identified the following problems: To address these problems, we extended the code smell term to the context of agility assessment, introduced the agile smell metaphor to denote a situation that may harm the adoption of an agile practice and proposed an agility assessment approach that automatically (or semi-automatically) detects agile smells in agile projects. The thesis produced the following contributions: To validate the solution, we conducted 2 case studies that aimed at detecting agile smells in agile projects. The resulting contributions addressed the problems identified in the existing agility assessment approaches and the reports generated in the case studies confirmed that the proposed approach, along with the other contributions, was able to automatically detect agile smells in the assessed agile projects.